2016
DOI: 10.1017/s0950268816000364
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and extrapulmonary tuberculosis: site distribution and risk of mortality

Abstract: Summary Scarce data exist on the relationship between diabetes and extrapulmonary tuberculosis (EPTB). We evaluated whether diabetes impacts site of TB and risk of death in patients with EPTB. We evaluated a cohort of TB cases from the state of Georgia between 2009 and 2012. Patients aged ≥16 years were classified by diabetes status according to medical records. Site of EPTB was determined by culture and/or state TB classification. Death was defined by all-cause mortality. Of 1325 eligible reported TB cases, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
10
17
1
Order By: Relevance
“…According to a 2016 CDC report, high rates of TB cases overall and TB cases attributable to extensive recent transmission were identified frequently among people experiencing homelessness within the past year and residents of a correctional facility at the time of diagnosis 28 . However, EPTB was more common in non-homeless patients than in the homeless, as previously reported 5 , 17 . The number of homeless cases was significantly higher in PTB (5.8%) than in exclusively EPTB (2.4%) in our population.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…According to a 2016 CDC report, high rates of TB cases overall and TB cases attributable to extensive recent transmission were identified frequently among people experiencing homelessness within the past year and residents of a correctional facility at the time of diagnosis 28 . However, EPTB was more common in non-homeless patients than in the homeless, as previously reported 5 , 17 . The number of homeless cases was significantly higher in PTB (5.8%) than in exclusively EPTB (2.4%) in our population.…”
Section: Discussionsupporting
confidence: 72%
“…The observed demographics of female gender and foreign-born origin in the USA have been previously reported as risk factors for EPTB 5 , 12 , 17 , 19 , 20 . Similarly, we found that female gender and Hispanic ethnicity were associated with patients who presented with exclusively EPTB after adjusting for other confounding factors.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This is attributed to the weak immunity of this group of patients. According to a study published recently, diabetes was common in patients with EPTB 10 .…”
Section: Discussionmentioning
confidence: 99%